2014
DOI: 10.1159/000362370
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Modulation of Autoimmune Responses in Multiple Sclerosis and Experimental Autoimmmune Encephalomyelitis: Therapeutic Implications

Abstract: Multiple sclerosis (MS) is a prototypic autoimmune inflammatory disorder of the central nervous system (CNS). MS pathogenesis is a complex phenomenon that is influenced by genetic and environmental factors that lead to the dysregulation of immune homeostasis and tolerance. It has been shown that pathogenic T lymphocyte subsets, such as T helper 1 (Th1) and Th17 cells, play a crucial role in the autoimmune cascade influencing disease initiation, progression and subsequent tissue damage during MS. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 161 publications
(176 reference statements)
0
30
0
2
Order By: Relevance
“…Other T cell subsets analyzed did not demonstrate any changes in cytokine production at the population level. Initially, IFN-γ was considered the key pathogenic cytokine in MS, but its role in the disease has been questioned during recent years (1, 35, 36). However, a number of findings support a disease-promoting role for this cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Other T cell subsets analyzed did not demonstrate any changes in cytokine production at the population level. Initially, IFN-γ was considered the key pathogenic cytokine in MS, but its role in the disease has been questioned during recent years (1, 35, 36). However, a number of findings support a disease-promoting role for this cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical onset of MS in patients usually manifests in their 20s and 30s and affects women about twice as often as men. While the etiologies in MS are hotly debated, the evidence obtained from animal models and patient studies indicated that abnormalities in the activity of different types of lymphocytes and the accompanying dysregulation of inflammatory cytokines play a crucial role in the pathogenesis of MS (Mastorodemos et al, 2015). So far, there has been SIGNIFICANCE Current therapeutic approaches can only ameliorate the clinical symptoms or reduce the frequency of relapse in multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) is an animal model of multiple sclerosis (MS) [19]. EAE is also an inflammatory disease induced by CD4 + T cells [20].…”
Section: Introductionmentioning
confidence: 99%